A conceptual framework for measuring e-Banking service quality and customer satisfaction: Integrating SERVQUAL and TAM in the context of Nepal - Paudel, Ram; Shrestha, Laba Kumar; Paudel, Rajesh (Journal of Economics and Business Letters, 2024)
This conceptual paper develops a comprehensive framework of the analysis of the service quality and customer satisfaction in the e-banking industry of Nepal by modifying the SERVQUAL model with the Technology Acceptance Model (TAM). Despite the spread in e-banking adoption, especially in urban areas, the quality of digital services is still uneven, and it can be explained by the lack of infrastructure, digital literacy, and the existing security issues. The suggested framework integrates five fundamental SERVQUAL dimensions, i.e., reliability, responsiveness, assurance, tangibles, and empathy with TAM constructs, such as trust, perceived usefulness, and perceived ease of use. The trust is set as a mediating variable, and the access to digital infrastructure is appointed a contextual moderator. The purpose of the study is to provide a formal foundation of further empirical verification, using, say, the structural equation modelling. The proposed framework provides a theoretical approach to improving the digital banking strategy and creating user trust and thus can enhance inclusive financial participation in developing economies like Nepal